Coherence in defect evolution data for the ion beam irradiated graphene - Yeo, Sunmog; Han, Jiyoon; Bae, Sukang; Lee, Dong Su (NATURE PUBLISHING GROUP, 2018)
The defect evolution in graphene produced by ion beam bombardment is investigated by changing the ion species, irradiation energy and dose. Raman spectroscopy is performed to examine the defect yield produced under various ion beam bombardment conditions. The defect yields of the vacancy-type defect are well described by the linear energy transfer (L) and dose (d). By increasing Ld, the defect yields exhibit similar behaviours for all ion species. As a consequence, all the defect yields can be collapsed into a single curve by multiplying them by a single parameter, suggesting that the defect evolution under various ion beam bombardment conditions can be described in a simple formula.
Keywords: ELECTRICAL-PROPERTIES; ELECTRONIC TRANSPORT; RAMAN